(untitled) (Perner’s Contacts, 2009)
Due to the increasing customer demands for quality traffic, increasing transport volumes and diverse range of possible technologies, logistics provides solutions in freight transport. This article focuses on logistics and information technology, market principles and new trends in the City logistics. Currently, it is important to solve the transport service in the City logistics, distribution models which are a guarantee of new opportunities for optimization of transport in urban areas.